Cytotoxicity Test of Green Betel Leaf Ethanol Extract (Piper Betle L.) Using Shrimp Larvae (Artemia Salina L.) Using The Brine Shrimp Lethality Test (BSLT) Method - Mardhiyah Adawiyah Ismail; Sri Vitayani; Nur Aulia Amir; Yusriani Mangarengi; Marzelina Karim; Mahry Galagher (International Journal of Health and Pharmaceutical (IJHP), 2025)
The Brine Shrimp Lethality Test (BSLT) method is a preliminary method for screening anticancer compounds by looking at the cytotoxic effect of a sample that will be tested on Artemia salina shrimp larvae. This study aims to evaluate the cytotoxic effect of ethanol extract of green betel leaves (Piper betle L.) on Artemia salina Leach larvae using the Brine Shrimp Lethality Test (BSLT) method. Extraction was carried out by maceration method using 96% ethanol, and phytochemical screening to show the presence of secondary metabolite on green betel leef. Cytotoxicity tests were carried out at five extract concentrations (concentrations of 50 ppm, 100 ppm, 250 ppm, 500 ppm, and 750 ppm). Based on the results of the research carried out, it can be concluded that the results show that the percentage of larvae deaths ranges from 30-80% and the highest mortality was obtained at a concentration of 750 ppm with a total of 26 larval deaths, this death was in line with the increase in concentration. The Lethal Concentration (LC50) value obtained was 121.3317 ppm. In conclusion, green betel leaf extract contains secondary metabolite compounds which cause cytotoxic effects on Artemia salina Leach shrimp larvae with a mortality percentage of 30-80% and the LC50 value is 121.3317 ppm.